Sistem Pendukung Keputusan Pemberian Uang Pertanggungan Terhadap Claimer Asuransi Kesehatan Menggunakan Metode SAW - Dedi Setiawan Halawa; Fristi Riandari (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2021)
DSS can provide interactive tools that allow decision makers to perform various analyzes of the available models. There are several methods used in DSS and one of them is the Simple Additive Weighting (SAW) method. The criteria used in determining the sum insured are length of stay, accidents and medical expenses. The application system can only provide recommendations for the provision of sum assured for health insurance claims at PT. Jasindo Health Care. The formulation of the research problem is to apply the Simple Additive Weighting (SAW) method in determining the award of sum insured to health insurance claimers using the PHP programming language, database, mysql. The calculation results show that Alternative A1 has the highest V value, namely V1 = 100, so alternative A1 is the most entitled to receive the sum insured against health insurance claimers at Jasindo Health Care.